Invasive mucinous adenocarcinoma of the lung presenting as a large, thin-walled cyst: A case report and literature review - Masuzawa, Keita (Mol Clin Oncol, 2017)
Invasive mucinous adenocarcinoma (IMA), formerly referred to as mucinous bronchioloalveolar carcinoma, is a rare variant form of invasive adenocarcinoma and is radiologically characterized by dense pneumonic consolidation, ground-glass opacity and nodules. By contrast, large, thin-walled cysts are rare. We herein report the case of a 75-year-old man with IMA presenting as a large, irregularly shaped cystic lesion. The histological diagnosis was based on specimens obtained during a bronchoscopy. The patient underwent lobectomy followed by anticancer chemotherapy for residual intrapulmonary metastases. Of note, the small metastatic nodules transformed into cystic lesions with thin walls and fused, forming a large, multiloculated cystic lesion. Typical pneumonic consolidation appeared in the pericystic parenchyma later during the clinical course. The available literature on this rare radiological manifestation was also reviewed and discussed. Clinicians should be aware of thin-walled cystic lesions as they may be an unusual radiological finding in IMA.